Forty-four years of land use changes in a Sardinian cork oak agro-silvopastoral system: a qualitative analysis - Sedda, Luigi; Delogu, Giuseppe; Dettori, Sandro (The Open Forest Science Journal, 2011)
The island of Sardinia is the biggest producer of natural cork in Italy. In this study, cork oak cover change is investigated in a typical agro-silvopastoral system where the main activities are cereal fodder and wheat cultivation, sheep rearing and cork exploitation. The research method is based on the comparison of two land use maps produced by photo-interpretation of digitised aerial photographs taken in 1954 and 1998, combined with interviews with local farmers, field surveys, and data collected from literature, administrative documentation and decadal censuses (at council level). The results show that the cork oak woodland surface decreased (-29%). It was substituted by other forest, ploughed land, and mixed grassland and shrubland. Apart from the transformation of the cork oak woodland to other forest, other changes have happened probably because of an increase in agricultural and pastoral activities as described by the documental material available for the same area
Keywords: aerial photography classification; agro-forestry; Cork oak; forest cover; land use; multi-temporal analysis; Sardinia

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Improving satellite images classification using remote and ground data integration by means of stochastic simulation - Carvalho, Julia; Soares, Amilcar; Bio, Ana (International Journal of Remote Sensing, 2006)
A methodology is proposed, to assess land surface cover classification using a geostatistical methodology of stochastic simulation, direct sequential cosimulation, to combine field observations with remotely sensed data classified with the classical algorithm of maximum likelihood classification. This procedure has two main advantages: (1) incorporation of a spatial continuity statistics; and (2) integration of different scales of information, contained in polygons (training areas) and point information (field observations), which also involves different qualities of information that is less reliable and more reliable, respectively. Moreover, this methodology allows production not only of a classified map, but also of maps of occupation proportions and of uncertainty for each thematic class. Local co-regionalization models are applied to account for local differences in both field data availability and distribution, and the correlation between these hard data and the classified satellite images as soft data. The methodology is based on two criteria: the influence of the hard data dependent on their availability and proportional to their proximity; and the influence of the soft data dependent on their local correlation to the hard data. The method is applied to a study of four economically important forest tree species on the Setu´bal Peninsula (south of Lisbon, Portugal). The results show more contiguous forest covers, i.e. more spatial contiguity, than the classical classification. In comparison to a contemporary field inventory, the proposed method improved forest cover estimations, showing a difference of only 3%.
Keywords: CODSS (voyant); forest cover; land cover classification; Maximum likelihood classification; stochastic simulation

Improving satellite images classification using remote and ground data integration by means of stochastic simulation - Carvalho, Julia; Soares, Amilcar; Bio, Ana (International Journal of Remote Sensing, 2006)
A methodology is proposed, to assess land surface cover classification using a geostatistical methodology of stochastic simulation, direct sequential cosimulation, to combine field observations with remotely sensed data classified with the classical algorithm of maximum likelihood classification. This procedure has two main advantages: (1) incorporation of a spatial continuity statistics; and (2) integration of different scales of information, contained in polygons (training areas) and point information (field observations), which also involves different qualities of information that is less reliable and more reliable, respectively. Moreover, this methodology allows production not only of a classified map, but also of maps of occupation proportions and of uncertainty for each thematic class. Local co-regionalization models are applied to account for local differences in both field data availability and distribution, and the correlation between these hard data and the classified satellite images as soft data. The methodology is based on two criteria: the influence of the hard data dependent on their availability and proportional to their proximity; and the influence of the soft data dependent on their local correlation to the hard data. The method is applied to a study of four economically important forest tree species on the Setu´bal Peninsula (south of Lisbon, Portugal). The results show more contiguous forest covers, i.e. more spatial contiguity, than the classical classification. In comparison to a contemporary field inventory, the proposed method improved forest cover estimations, showing a difference of only 3%.
Keywords: CODSS (voyant); forest cover; land cover classification; Maximum likelihood classification; stochastic simulation

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer

Distribution of an increasing roe deer population in a fragmented Mediterranean landscape - Tellería, José Luis; Virgós, Emilio (Ecography, 1997)
This paper describes roe deer Capreolus capreolus distribution in central Spain, where the species has spread from the mountains into peripheral agricultural areas In this region, it is more abundant in forest fragments near the mountains than in those further away, in pine and oak woodlands than in sclerophyllous forests, and in forests with open water than in those lacking this resource The paper also analyzes whether habitat quality and geographic location of forests with respect to roe deer source areas are the two basic causes of its distribution, as predicted by some models of the species distribution in fragmented landscapes The results corroborate this hypothesis revealing that roe deer abundance is linked negatively to sclerophyllous forest cover and distance from mountains We conclude that this type of farmland seems to be sub-optimal for roe deer in comparison with forested, moist mountains
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: abundance; Distribution patterns; forest cover; habitat quality (voyant); roe deer